8x-(7x+3)=8x-24

Simple and best practice solution for 8x-(7x+3)=8x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-(7x+3)=8x-24 equation:


Simplifying
8x + -1(7x + 3) = 8x + -24

Reorder the terms:
8x + -1(3 + 7x) = 8x + -24
8x + (3 * -1 + 7x * -1) = 8x + -24
8x + (-3 + -7x) = 8x + -24

Reorder the terms:
-3 + 8x + -7x = 8x + -24

Combine like terms: 8x + -7x = 1x
-3 + 1x = 8x + -24

Reorder the terms:
-3 + 1x = -24 + 8x

Solving
-3 + 1x = -24 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-3 + 1x + -8x = -24 + 8x + -8x

Combine like terms: 1x + -8x = -7x
-3 + -7x = -24 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3 + -7x = -24 + 0
-3 + -7x = -24

Add '3' to each side of the equation.
-3 + 3 + -7x = -24 + 3

Combine like terms: -3 + 3 = 0
0 + -7x = -24 + 3
-7x = -24 + 3

Combine like terms: -24 + 3 = -21
-7x = -21

Divide each side by '-7'.
x = 3

Simplifying
x = 3

See similar equations:

| 5(x-1)=3x-15 | | -6(3p+3)-18=5(4p+8) | | 1/6y=5/33 | | 18x+25=6(3x-4) | | 2=p/2-1 | | t+2t=12 | | x=6+0.125y | | 20*x+83=223 | | 2(x+6)=8x+-6x+4 | | 2x+7y=475x+4y=50Findxy | | 5m+25=9m-3 | | 5x+3=2(x+3)+3x-3 | | 2+1/3t=1+1,3 | | 5(y-1)=3x-15 | | 8x-(4x+3)=13 | | 3/30=n/80 | | 5x+3=2(x+3)+3x | | 17=w/5-8 | | w/2-(-8)=10 | | x-1/6+1/3 | | 7x+11+10=0 | | 8x+3=-19 | | 25=2(x-3) | | 6(7-2x)=12+3(x-5) | | 1=b/4-8 | | d+d+3=17 | | 2m+5=5m-4 | | 3s+5s=1-8s | | 9x-3+2x-3=9x | | -13=t/2-16 | | 7n+5n=36 | | -6n+6=-4n-14 |

Equations solver categories